Negotiating Gender and Religion: Comparative Perspectives from Judaism and Islam. - Anteby-Yemini, Lisa (Journal of Feminist Studies in Religion (Indiana University Press))
Women in Orthodox Judaism and mainstream Islam are discriminated against in Muslim and Jewish family law; subjected to rulings elaborated by men regarding female purity and reproductive rights; segregated in the spaces of synagogues and mosques; and excluded from advanced study, interpretation of religious law (fiqh and halakha), and spiritual leadership. Gender-nonconforming believers have no place, either. Nonetheless, since the mid-twentieth century, Jewish and Muslim women as well as sexual minorities have been making claims for gender justice, attempting to change from within these conservative religions. The article shows convergences and divergences in women's strategies to undermine male hegemony on religious authority in both faiths. If numerous works have dealt with female agency and resistance to patriarchy in each tradition, comparative studies are still lacking, and this article suggests areas in family law, ritual purity, and procreation to further feminist and queer interreligious research.